2017
DOI: 10.1007/s00455-017-9816-0
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Corpus Callosum in Pediatric Dysphagia: Preliminary Findings from a Diffusion Tensor Imaging Study in Children with Unilateral Spastic Cerebral Palsy

Abstract: The purpose of this study is to determine the relationship between the structural integrity of the corpus callosum (CC) and clinical feeding/swallowing performance in children with unilateral spastic cerebral palsy (USCP). Twenty children with USCP, (11 males, 5.11-17.6 yoa) were assessed via the Dysphagia Disorder Survey (DDS) and diffusion tensor imaging. Children were grouped into left hemisphere lesion (LHL; n = 13) and right hemisphere lesion (RHL; n = 7) groups. DTI variables analyzed for three CC region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 58 publications
0
45
0
2
Order By: Relevance
“…The DMSS was used for this study as it provided data regarding presence/absence of dysphagia in all participants. Neither of these two studies clearly reported the time of dysphagia assessment after unilateral CP diagnosis.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…The DMSS was used for this study as it provided data regarding presence/absence of dysphagia in all participants. Neither of these two studies clearly reported the time of dysphagia assessment after unilateral CP diagnosis.…”
Section: Resultsmentioning
confidence: 96%
“…Across the five included studies, there were 411 participants ranging from sample sizes of 14 to 248 (Table ). Three studies included patients from the United States, one from Poland, and one was conducted in Canada but enrolled patients from 10 different countries using an international registry…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…При этом показатели фракционной анизотропии этих структур статистически значимо коррелируют с тяжестью двигательных нарушений при одной из самых распространенных форм ДЦП -спа-стической диплегии [27]. Высказывается мнение, что сниженный КФА именно мозолистого тела, а не кортикоспинальных трактов является точным индикатором моторного дефицита у детей с ди-плегической формой ДЦП, особенно в отношении тонких мануальных навыков [24,29,46]. Мозоли-стое тело при ДЦП тоньше, чем у неврологиче-ски здоровых детей, что соотносится с диффуз-ной потерей всего белого вещества полушарий мозга.…”
Section: зак лючениеunclassified